Funcionalidad familiar y su relación con las conductas de riesgo para trastornos de conducta alimentaria en adolescentes de Bachillerato. Zona 7, Ecuador. - Íñiguez Ordoñez, Carlos Eri (2017)
Eating disorders are considered alterations in the behavior of the person, related to food which causes a significant deterioration of physical health or biopsychosocial functioning; It is from multifactorial etiology and which significantly and especially affects adolescents; for which a descriptive, analytical, cross - sectional study was carried out to evaluating family functionality in relation to risk behaviors for eating disorders in adolescents of the baccalaureate of the Zone 7; through and ramdomized sample of 960 students from 15 to 19 years of age; The instrument used was the food attitudes test (EAT-26) and the evaluation of domestic relations (FFSIL). Among the results, the general prevalence for presenting risk behaviors for eating disorders was 25,3%; with an average of 17 years of age. In dysfunctional families, the risk for ED was 27,2%, in relation to the functional families of 34,2%; being higher in women with 29,9% of low life conditions. To conclude, there is no stastiscal significance (p> 0,05) between the diagnosis of family functionality and risk behaiors of ED, but there is statistical significance (p< 0,05) between the dimensions: communication, adaptability, oral control and food concern for the risk of ED. Key words: Eating Disorders, Adolescence, Family, Bulimia, Anorexia.